Kewujudan Doktrin Non-Triniti dalam Ajaran Kristian: Kajian Terhadap Kenyataan al-Kitab (Bible) - Ahmad, Mahmud; Mohd Hambali @ Khambali, Khadijah; Senin, Nurhanisah (Jurnal Usuluddin, 2010)
This paper highlights some irnportant discttssion on the school and the chtrrch that reiects the doctrine o.f- Trinity, *-ho is os ktto*-n in this stud,v as a nrtn-Trinitarian Chrislianit.v. The disptne on the issue o.f divinity in Christianity which was presented by dffirent non-Trinitat'ian group,t and chw'ches has beconte a basis issue either accepting or reiecting the authoriqv- of the Bible in Christianity. Various perceptions arose on the ac:tual belief oJ 'divini\t oJ'God'in Christianity when the Bible has been c:tttttprehensive revietved by non' Trinitarian groups attd chw'ches. With the arguments of rejection tov:ard the doctrine of Trinity b-v everyt school and church, this study as clelves into detail of the maior statentents of 'divittity'in the Bible either.from the Old Testament or New' Te,stantent in detail. Overall, the reiection of the doctt'ine o/ Trinity is based on two main elements; rejec:tion oJ'the doctrine that set out clearly by the Bible cmcl the belief that i,s di/.ficult to understand what made sense